Phenomenology of Collective Will in the Management of Shared Agricultural Land Plots - Aleksandrovich Mayboroda, Victor (International Journal of Engineering and Technology, 2018)
This paper addresses the advent of a new stage in the development of relationships associated with the management of agricultural land plots that are in shared ownership. The social group that emerged based on principles of the initial privatization, which was characterized by value-based unity based on collective labor in agricultural production, has, in the course of time, been supplanted by a new type of owners â€“ those not characterized by value-based unity. The method for managing a common property â€“ through general meetings â€“ remains the same. There has yet to be put in place a legal instrument for dealing with the socially inhomogeneous makeup of the owners group that would make it possible to form the collective will of general meetings in accordance with the objectives for managing a property, as the very inhomogeneity of the makeup precludes the possibility of unity of management objectives. In this situation, the phenomenon of collective will lacks proper legal protection from usurpation by an economically strong entity. In this regard, the author proposes carrying out a differentiation of the types of disputes and procedural methods for resolving those disputes.Â Â Â